Unia Europejska – na drodze do mocarstwowości - Łukasik, Przemysław (Forms of Power in Contemporary World – Case Studies, 2023)
The European Union faces a dilemma of playing the role of a serious world leader or falling into marginalization, which will result in a bipolar world (USA, PRC). The EU soft power, i.e. peace and development, is to be extended by European decision-makers to include hard power, i.e. the creation of a defense community. The aim of the text is to look at the prospects and conditions for the formation of the EU as a world leader in the 21st century.